707 Discovery of a novel EP2 and EP4 dual antagonist. (10th December 2020) - Lee, Yeri; Kim, Hyun Jin; Kim, Donggeon; Lee, Joo Youn; Yun, Chang Soo; Lee, Hyuk; Shin, Young Sook; Han, Soo Bong; Lim, Sang Kyun
Abstract : Background: Prostaglandin E2 (PGE2) is one of the most abundant prostaglandins, with crucial roles in normal and pathologic physiology. Especially, PGE2 levels are abnormally elevated in many cancers, and high levels of PGE2 are known to be pro-tumorigenic, likely due to the immune suppressive effect in the tumor microenvironment. 1–4 There are four types of PGE2 receptors; EP1, EP2, EP3 and EP4. Among them, EP2 and EP4 activate adenylate cyclase and increase cAMP levels, which induce the cAMP-dependent protein kinase (PKA) signaling pathway. EP2 and EP4 are expressed in various immune cells (e.g. macrophages, dendritic cells, NK cells and CTLs), and genetic and pharmacological inhibition of EP2 and EP4 increases immune activity and suppresses tumor growth. Methods: To evaluate the binding affinity against EP2 and EP4, a radioligand binding assay was conducted using EP2 or EP4 transfected HEK293 cells. Cell membrane homogenates were incubated with [3H]PGE2 in the absence or presence of the test compounds. Following incubation, the samples were filtered rapidly under vacuum through glass fiber filters and rinsed several times with cold Tris-HCl. The filters were dried then counted for radioactivity in a scintillation counter using a scintillation cocktail. The results were expressed as a percent inhibition of the control radioligand specific binding.The antagonistic activity against EP2 and EP4 was assessed via LANCE Ultra cAMP assay (PerkinElmer). HEK293 cells overexpressing EP2 or EP4 were seeded into the plate and treated by PGE2 and compounds. After 30 minutes of incubation, cAMP levels were measured by FRET signal using Varioskan plate reader, following the manufacturer's protocol.Anti-tumor activity of KT-00113 was evaluated using LLC1 syngeneic model. When tumor volume reached approximatively 100 mm 3, mice were treated PO, QD. Tumor size was measured twice every week. Results: Systematic structure-activity relationship (SAR) investigation identified novel EP2 and EP4 dual antagonists. The most promising compound KT-00113 possesses high potency against both EP2 and EP4, while maintaining high selectivity over other prostanoid receptors. In vitro and in vivo ADMET studies show that KT-00113 has a favorable profile, apt for further examination in in vivo cancer models and immune cell function in tumors. Conclusions: KT-00113, a highly potent and selective EP2/4 dual antagonist has strong potential to become the best-in-class immune suppression lifting cancer immunotherapy and may be suitable for further development in a clinical setting. References: Cordes T, Hoellen F, Dittmer C, Salehin D, Kummel S, Friedrich M, Koster F, Becker S, Diedrich K, Thill M. Correlation of prostaglandin metabolizing enzymes and serum PGE2 levels with vitamin D receptor and serum 25(OH)2D3 levels in breast and ovarian cancer. Anticancer Res ;32 ( 2012):351–357. Diakowska D, Markocka-Maczka K, Nienartowicz M, Lewandowski A, Grabowski K. Increased level of serum prostaglandin-2 in early stage of esophageal squamous cell carcinoma, Arch Med Sci ( 2014);10 :956–961. Akbari N, Ghorbani M, Salimi V, Alimohammadi A, Khamseh ME, Akbari H, Nourbakhsh M, Sheikhi A, Taghavi SF, Tavakoli-Yaraki M. Cyclooxygenase enzyme and PGE2 expression in patients with functional and non-functional pituitary adenomas. BMC Endocr Disord 2020;20 :39. Gomes RN, Felipe da Costa S, Colquhoun A. Eicosanoids and cancer, Clinics (Sao Paulo), 73 ( 2018) e530s.